A SYSTEMATIC LITERATURE REVIEW: FINANCIAL SOCIALISATION AND FINANCIAL LITERACY AMONG UNIVERSITY STUDENTS WORLDWIDE - Ahmad Muhaimin Mat Jusoh; Muhammad Faizal A. Ghani (Journal of Islamic, Social, Economics and Development, 2023)
This paper discusses a thorough literature evaluation conducted over the previous ten years on the subject of financial Socialisation and financial Literacy among university students globally. This study was conducted to examine the distribution of studies of financial socialisation and financial literacy among college and university students in terms of year of publication, the study context covered in previous studies, the context of study areas used, the focus and trends of previous studies, and the research methods used in previous studies. This review study followed the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) to analyse articles from Scopus and Web of Science. In terms of publication trends, the analysis reveals that financial literacy is more prevalent and, on the rise, than financial socialisation, due to financial socialisation has not yet reached its full potential. In addition, past research has demonstrated a greater interest in researching financial literacy than financial socialisation. Prior research has similarly favoured quantitative study designs for implementation. The research instruments utilised in a study include questionnaires and tests.